Hands on Alemtuzumab-experience from clinical practice: whom and how to treat. Issue 1 (December 2016) - Hassoun, Lina; Eisele, Judith; Thomas, Katja; Ziemssen, Tjalf
Abstract Alemtuzumab is a monoclonal antibody, which was recently approved for the treatment of active relapsing remitting multiple sclerosis. Its main mechanism of action is based on targeting CD52, an antigen of unknown function which is found on B and T lymphocytes, leading to depletion followed by repopulation of these cells. The high efficacy of Alemtuzumab in controlling relapsing remitting MS has been shown in several clinical trials. This new therapy approach is associated with a specific side effects profile requiring regular longterm monitoring. The most important side effects are infusion-associated reactions, a slight increase of infections as well as autoimmune events in almost one third of treated patients. Based on two years of clinical experience in Germany, this review covers the first steps with the careful patient selection to be treated with Alemtuzumab over the preparation steps and the infusion courses up to the longterm monitoring after Alemtuzumab treatment.